PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PT DIPA PUSPA LABSAINS JAKARTA - Agung Tri Putranto; Putri (Al Hasanah Barokah Foundation, 2025)
The purpose of this study was to determine the effect of education and training on employee performance at PT Dipa Puspa Labsains Jakarta in a manner. The research method used is quantitative descriptive, the population is all employees of PT Dipa Puspa Labsains Jakarta, which is 40 people and uses a saturated sample technique because the number of populations is used as a sample. Data collection techniques use observation, interviews and questionnaires. The analysis method uses the validity test method, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis, hypothesis test. The results of this study are the Effect of Education and Training on Employee Performance at PT. Dipa Puspa Labsains, Jakarta, can be seen in the results of the multiple correlation coefficient value of 0.612. This means that there is a strong positive relationship between education and training on employee performance. The determination test between education and training on performance is 57%, which means that education and training contribute 57% while the remaining 43% is influenced by other variables unknown to the author. The results of multiple regression tests between education and training on performance are that if education increases by one unit, it will increase employee performance by 0.290 and if training increases by one unit, it will increase employee performance by 0.324. And if education and training (X1 and X2) do not exist = 0, then the performance value (Y) still exists at = 22.188. So the regression equation is Y = 22.188 + 0.290 (X1) + 0.324 (X2). The significant test is obtained from tcount = 4.040, thus, if tcount> table, namely 4.040> 2.026, which means H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between education and training on employee performance at PT. Dipa Puspa Labsains, Jakarta.